The Legal Isomorphism in Indonesian Constitutional Amendment: Interplay Between Foreign Influence and National Identity - Azhari, Aidul Fitriciada; Rizka, Rizka; Setiawati, Diana; Almira, Sekar Diah Ayu; Salmande, Ali (Jurnal Hukum, 2025)
The post-authoritarian reform era in Indonesia (starting in 1998) was characterized by a push to democratize the state system, leading to the adoption of several foreign, democratic, or "globalized" constitutional concepts. This process demonstrates legal isomorphism where Indonesia aligned its constitutional framework with prevailing international democratic standards. This article analyses the patterns of legal isomorphism in the Indonesian constitutional amendment by examining the dynamic interplay between foreign influence and national identity. For that reason, the research aims to determine a legal isomorphism that can harmonize and balance both foreign influences and the desire for a national identity in the constitutional amendment in Indonesia. To achieve these objectives, the study employed a qualitative research method with a socio-legal and comparative law approach. The research finds three distinct patterns of coercive legal isomorphism concerning the constitutional amendment process in Indonesia. Meanwhile, comparatively, a mimetic isomorphism regarding unamendable provisions of basic structure can be considered for harmonizing and making a balance between foreign influences and national identity in the constitutional amendment. The novelty of this research lies in its identification and classification of legal isomorphism patterns within Indonesia’s constitutional amendments, providing a new perspective on how external legal influences interact with national identity. This study contributes to the broader discourse on constitutional development by offering a framework for analysing the complex relationship between global legal trends and domestic constitutional transformations.